VALUATION AND BUSINESS PERFORMANCE ANALYSIS OF PT. IMC PELITA LOGISTIK .TBK (PSSI) - Pandumulia Segalapuja Hasayangan; Isrochmani Murtaqi; Oktofa Yudha Sudrajad (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study investigates the valuation and financial performance of PT. IMC Pelita Logistik Tbk. (PSSI), a player in Indonesia's shipping and logistics industry. Using an absolute valuation method with Free Cash Flow to the Firm (FCFF) and Weighted Average Cost of Capital (WACC), PSSI's intrinsic value per share was determined to be US -0.0391, significantly below its market price of US 0.0278, indicating that the stock is overvalued. For relative valuation, the metrics used were Price to Earnings Ratio (PER), Price to Book Value (PBV), and Enterprise Value to EBITDA (EV/EBITDA). PSSI's PER (3.56) is lower than its peers (6.43), but its PBV (0.86) and EV/EBITDA (3.18) are higher than the average of its peers (0.68 and 2.33), indicating overvaluation. The author prioritizes EV/EBITDA as it provides a more comprehensive assessment compared to PER. The financial performance analysis includes profitability, liquidity, activity, and solvency ratios. The final recommendation for investors is to sell, as PSSI is overvalued based on absolute valuation, PBV, and EV/EBITDA metrics.